INVESTIGATION OF SOME FACTORS' EFFECTS ON PATIENTS' NEED OF INFORMATION (GAZIANTEP EXAMPLE - BOZKURT, ibrahim (Göbeklitepe Medical Science Journal, 2021)
In this study, it is aimed to examine the effects of hospital experience, researching about hospital and disease, being informed by healthcare professionals, and participating in an organized training program in terms of meeting the information needs of patients about health services and diseases. For this purpose, the survey data applied to 855 patients receiving health services in public and private hospitals serving in Gaziantep Province were analyzed using frequency distribution, factor analysis, independent sample t-test, and f test (Anova). According to the analysis results; It was determined that the information needs of the participants about their diseases and health services are at a high level. Participants who attend an organized training program and those who are informed about their diseases need more information. It has been determined that researching before applying to the hospital reduces the need for information about the providers and qualifications of the healthcare service, but does not cause any change in disease and related issues. Besides, it was understood that the previous experiences of the participants about the hospital and the physician did not contribute to the need for information.